Repositioning of Tourism and Recreational Industry in Africa: The Case of Shrines and Sacred Places in Nigeria - Bienose-Osagiede, Belinda U.; Eze, Christian C.; Philip, Philip Amah (NIU Journal of Social Sciences, 2023)
Heritage preservation brings a people’s history and historic places back to their collective consciousness. Countries that have adopted tourism as a means of sustaining their economies understand that their heritage is the very essence and fabric of the people’s existence and identity. It was discovered that despite the importance of this cultural heritage to national economic development and identity preservation, the majority of Africans have abandoned African traditional religion, Shrines have been left to crumble and sacred places destroyed. Many traditional rituals have fallen into disuse and various cult objects and symbols of African traditional religion are being eroded and modified as a result of the onslaught of combined forces of the agents of religious change. The work finds out that traditional shrines and sacred places can act as a hook to attract tourists. Thus, exploring the traditional shrines and sacred places in Nigeria to promote tourism cannot be over-emphasized. This can be envisaged by analyzing its impact in various areas of life. Traditional shrines and sacred places if well preserved can attract visitors to a destination who spend money within the community, enhancing the local economy and supporting the local economy through restaurants, hotels, and other tourism-selected businesses. The high inflow of tourists and day visitors into the community during such occasions contributes immensely to the economic empowerment of people through the injection of tourist expenditure into the community. Keywords: Shrines, Sacred places, tourism and recreational centres